2022
DOI: 10.1186/s12915-022-01491-0
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific expression of pheromones and other signals in gravid starfish

Abstract: Background Many echinoderms form seasonal aggregations prior to spawning. In some fecund species, a spawning event can lead to population outbreaks with detrimental ecosystem impacts. For instance, outbreaks of crown-of-thorns starfish (COTS), a corallivore, can destroy coral reefs. Here, we examine the gene expression in gravid male and female COTS prior to spawning in the wild, to identify genome-encoded factors that may regulate aggregation and spawning. This study is informed by a previousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 181 publications
3
33
0
Order By: Relevance
“…Furthermore, given the large number of neuropeptides (>40) that have been identified in A. rubens (Semmens et al, 2016), it is likely that other neuropeptides that remain to be investigated are also expressed in the gonoducts and/or gonads. Consistent with this hypothesis, transcriptomic and mass spectroscopic analysis of the starfish Acanthaster planci has revealed a variety of neuropeptides that are expressed in the gonads, including orthologs of neuropeptides analyzed in this study (SS1-type, PPLN1-type, PPLN2-type, and GnRH-type), and others (e.g., kisspeptin-type, luqin-type, orexin-type, SALMFamide-type, and NGFFYamide) (Jonsson et al, 2022;Smith et al, 2017).…”
Section: Comparative Physiology Of Neuropeptides As Regulators Of Rep...supporting
confidence: 85%
“…Furthermore, given the large number of neuropeptides (>40) that have been identified in A. rubens (Semmens et al, 2016), it is likely that other neuropeptides that remain to be investigated are also expressed in the gonoducts and/or gonads. Consistent with this hypothesis, transcriptomic and mass spectroscopic analysis of the starfish Acanthaster planci has revealed a variety of neuropeptides that are expressed in the gonads, including orthologs of neuropeptides analyzed in this study (SS1-type, PPLN1-type, PPLN2-type, and GnRH-type), and others (e.g., kisspeptin-type, luqin-type, orexin-type, SALMFamide-type, and NGFFYamide) (Jonsson et al, 2022;Smith et al, 2017).…”
Section: Comparative Physiology Of Neuropeptides As Regulators Of Rep...supporting
confidence: 85%
“…or in small (5000 litre) closed aquarium in artificial seawater (coelomocytes)-or (iii) type of RNA-Seq method, whether stranded RNA-Seq (Hall et al, 2017) or CEL-Seq2 (this study). Using the same tissue, and sampling and sequencing methods as described here, we found that these wild-captive differences are more than four times greater than gene expression differences observed between seasons (unpublished) and 173 times greater than between sexes (Jönsson et al, 2022). Only metamorphosis appears to have a similar magnitude of transcriptional change in echinoderms (Wygoda et al, 2014).…”
Section: Wild and Captive Cots Have Strikingly Different Gene Express...mentioning
confidence: 53%
“…For captive and wild coelomocyte samples (13 and eight biological replicates, respectively), CDS were considered expressed if the average count per condition was ≥0.25 (Jönsson et al, 2022). Using Wald Test statistics in the DESeq2 package (v1.28.1; Love et al, 2014), CDS with an adjusted p ‐value <.05 between treatments were identified as being significantly differentially expressed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples with mapped transcripts < 0.5 million were discarded as low-quality [60]. GBR v1.1 gene models and transcriptomes can be visualised at https://apolloportal.genome.edu.au/degnan/cots [28,29].…”
Section: Sampling Of Wild-caught Cots and Cel-seq2 Library Constructionmentioning
confidence: 99%